Elaboração de farinhas de flores de hibisco colibri (Malvaviscus arboreus Cav. ) e cunhã (Clitoria ternatea L.): aspectos físicos e morfológicos - Santos, Anna Izaura Balbino dos (2024)
Unconventional Food Plants (UFPs) have gained traction in both academic and gastronomic domains, driven by current trends towards healthier diets. The use of various UFPs as alternative sources of nutrients and minerals is increasingly prevalent in human nutrition. Species such as Malvaviscus arboreus (Turk's cap) and Clitoria ternatea (butterfly pea) are utilized for their nutritional and medicinal values across different cultures. This study aimed to develop and characterize flours derived from the drying of Malvaviscus arboreus and Clitoria ternatea flowers, focusing on their thermal, physical, and structural properties. Flowers were individually dried in a forced-air oven at temperatures of 50, 60, 70, and 80 °C, with drying kinetics analyzed and mathematical models applied to the data. The resulting flours were characterized for physical parameters, particle morphology via scanning electron microscopy (SEM), and thermal properties using thermogravimetric analysis (TG/DTG). The Logarithmic model best fit the drying kinetics of Malvaviscus arboreus, while the Page model provided the best fit for Clitoria ternatea. SEM revealed irregular structures with particles of varying sizes in both hibiscus and butterfly pea flours. Hibiscus flour exhibited more compact and regular particles, whereas butterfly pea flour showed more porous and irregular particles. Differences in the drying temperatures for the two flower species did not notably affect their structural characteristics.